Smart money strategy : your ultimate guide to financial planning - Smith, Luke (John Wiley & Sons, Inc., 2023)
Be your own financial planner and create a winning strategy to achieve your money goals Do you want to learn and apply the strategies that experts use to grow and protect wealth? In Smart Money Strategy, popular financial planner Luke Smith comprehensively reveals the principles, methods and tactics that real financial planners use with their clients. Every person's--and every family's--financial journey is different. There's no silver bullet or one-size-fits-all approach. But there are financial strategies that can be applied, no matter what stage you're at in life, to get your money working harder for you with less stress. Smart Money Strategy will help you to define your priorities and create a personalised, actionable plan to achieve your goals. You'll learn effective strategies to manage your income, reduce your debts, and maximise your investment, superannuation and retirement outcomes. Even better, you'll learn how different strategies can be stacked together for maximum benefit. In other words, you'll learn how you can stack the financial odds in your favour! You'll discover: The basics: 5 truths about money and the 5 foundations you need to get started The actual strategies used by financial planners when it comes to cash flow, risk assessment, investing, protecting wealth, retirement, and estate planning How smart planning can minimise fees and taxes on your investments How to combine your money strategies and put together your own detailed financial plan From adopting a money mindset to protecting your assets, with Smart Money Strategy you'll uncover the secrets to achieving your financial goals. Whether you want a hands-on DIY approach, or you're looking for the essentials you need to talk more confidently with your own financial planner, this book will help you create a tailored plan for growing your wealth.